Novel Ribonuclease Activity Differs between Fibrillarins from Arabidopsis thaliana - Rodriguez-Corona, Ulises; Pereira-Santana, Alejandro; Sobol, Margarita; Rodriguez-Zapata, Luis C.; Hozak, Pavel; Castano, Enrique (Frontiers in Plant Science, 2017)
Fibrillarin is one of the most important nucleolar proteins that have been shown as essential for life. Fibrillarin localizes primarily in the periphery between fibrillar center (FC) and dense fibrillar component (DFC) as well as in Cajal bodies. In most plants there are at least two different genes for fibrillarin. In Arabidopsis thaliana both genes show high level of expression in transcriptionally active cells. Here we focus on two important differences between A. thaliana fibrillarins. First and most relevant is the enzymatic activity by AtFib2. The AtFib2 shows a novel ribonuclease activity that is not seen with AtFib1. Second is a difference in the ability to interact with phosphoinositides and phosphatidic acid between both proteins. We also show that the novel ribonuclease activity as well as the phospholipid binding region of fibrillarin is confine to the GAR domain and represents a new role for this protein in rRNA processing.